Prognostic value of blood inflammatory composite markers in the survival of pediatric patients with secondary hemophagocytic lymphohistiocytosis - Luo, Nandu; Xie, Xin; Chen, Yan; Du, Zuochen; Huang, Pei (Frontiers in Pediatrics, 2025)
ObjectiveThis study aimed to explore the prognostic value of blood inflammatory composite markers in the survival of pediatric patients diagnosed with secondary hemophagocytic lymphohistiocytosis (sHLH).MethodsClinical data from 138 newly diagnosed sHLH patients hospitalized between January 2012 and October 2023 were analyzed. Receiver operating characteristic curve analysis was used to determine cutoff values and evaluate predictive accuracy, while Cox regression analysis was employed to identify prognostic factors.ResultsThe median age of the 138 sHLH patients was 38 months, with a female-to-male ratio of 0.92. Infection was identified as the most common cause of sHLH, 52.9% testing positive for the epstein-barr virus (EBV). Clinical features included decreased blood cell counts in 87.0% of patients, hypofibrinogenemia in 55.07%, hypertriglyceridemia in 46.38%, and elevated ferritin levels in 94.2%. Additionally, all patients experienced fever, while hepatomegaly and splenomegaly were observed in 66.67% and 76.81%, respectively. During the study, 48 patients died. Cox regression analysis identified red blood cell distribution width (RDW) ≥14.35%, fibrinogen <1.5 g/L, red blood cell distribution width to platelet ratio (RPR) ≥0.36, and lactate dehydrogenase to serum albumin ratio (LAR) ≥56.02 as significant predictors of decreased survival.ConclusionThis study provides preliminary evidence that accessible inflammatory markers like LAR and RPR may assist in early prognostic assessment of pediatric sHLH. These findings highlight the potential utility of routine blood parameters, warranting further validation in larger, stratified cohorts.